STUDY OF SERUM GGT LEVELS AND LIPID PROFILE IN DIABETIC PERIPHERAL NEUROPATHY - DR. B. JYOTHIRMAYI,; MR. SANJAYSETH,; MS. S. KAVIARASI,; DR. EBENEZER WILLIAM., (International Journal of Pharma and Bio Sciences, 2012)
Comparative study of gamma glutamyl transferase and lipid profile in diabetic patients with peripheral neuropathy and diabetic patients without any complications. Our study included 15 diabetic patients without any complications as control group and 30 diabetic patients with neuropathy as study group. Patients with history of alcoholism, acute and chronic illness were excluded from the study. The levels of GGT and HbA1C were significantly increased in study group when compared to control group. Even though levels of cholesterol, triglycerides LDL and VLDL are of not much significance, the atherogenic index ratio was calculated which was high in study group when compared to control group. Serum GGT can be used as an important marker in diagnosing diabetic peripheral neuropathy.